PENGARUH DESAIN KEMASAN, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Susu Kemasan Greenfields di Tangerang) - Putra, Muhammad Hasanudin Imam Yudia; Setyarko, Yugi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
In recent years, organic dairy products have received significant attention from consumers who are increasingly concerned with the design, image of the product and product quality. Researcher want to show and analyze the influence of packaging design, brand image and product quality on purchasing decisions for Greenfields dairy products. The population of this research is buyers of Greenfields dairy products at least once who live in Tangerang. The data source used in this research is primary data by distributing questionnaires. The sample in this study used a purposive sampling method with the Lemeshow formula and obtained 110 respondents. The analysis tool used is SPSS v.25 software. The results of this research show that packaging design does not have a significant effect on purchasing decisions, while brand image and product quality have a significant effect on purchasing decisions.